2008
DOI: 10.1007/s12033-008-9037-8
|View full text |Cite
|
Sign up to set email alerts
|

Possible Role of Light and Polyamines in the Onset of Somatic Embryogenesis of Coffea canephora

Abstract: The concentration of free and bound polyamines was studied during the somatic embryogenesis induction process in Coffea canephora explants. In the present study we show that when the induction of somatic embryogenesis in C. canephora is carried out under light conditions and in the presence of the plant growth regulator, benzylaminopurine, a cytokinin, a faster response to induction is obtained. In the darkness, the response is delayed for more than 20 days, and the number of embryos is smaller. In the absence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 63 publications
1
11
0
1
Order By: Relevance
“…They demonstrated that Put levels increased 27-32 fold in petiole derived tissue cultures growing in embryo induction medium and Put level fell sharply upon transfer of cultures to embryo differentiation medium. Increase in PA content during induction of SE was also reported by Clelia et al 2008 in Coffea caenophora. Furthermore, increase in PA content was detected in cultures of Citrus sinensis growing in embryo inducing medium.…”
Section: Introductionsupporting
confidence: 72%
“…They demonstrated that Put levels increased 27-32 fold in petiole derived tissue cultures growing in embryo induction medium and Put level fell sharply upon transfer of cultures to embryo differentiation medium. Increase in PA content during induction of SE was also reported by Clelia et al 2008 in Coffea caenophora. Furthermore, increase in PA content was detected in cultures of Citrus sinensis growing in embryo inducing medium.…”
Section: Introductionsupporting
confidence: 72%
“…Nevertheless, recent studies have shown the involvement of conjugated (Santa-Catarina et al 2007) and bound (De-la-Peña et al 2008) PAs in early stages of somatic embryo development in Ocotea catharinensis and Coffea canephora, respectively. Therefore, future investigations focused on monitoring conjugated and bound PAs content could help to gain a deeper vision of sugarcane embryogenic process during differentiation-maturation stage.…”
Section: Polyamines Contentmentioning
confidence: 99%
“…Successful induction of somatic embryo in light or dark condition was different among plants. Somatic embryogenesis can be achieved in dark condition (Tahardi et al, 2000;Gomes et al, 2006), dark condition followed by light treatment (Sunandar et al, 2017), or fully in light condition (de-la-Pena et al, 2008;Bakhshaie et al, 2010;Lema-Ruminska & Kulus, 2012). In tea micropropagation, light was also important to induce somatic embryogenesis (Akula et al, 2000, Akula & Dodd, 1998 and were in confirmation of the present results of successful induction of somatic embryogenesis when explants were culture on light condition.…”
Section: Introductionmentioning
confidence: 99%